The Contestation of Feminism and Religious Authority and Its Implication in Islamic Education - Ai Fatimah Nur Fuad; Alif Rizky Ramadhan (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2023)
Feminism and religious authority are two conceptual frameworks that have been subjects of discussion in the field of Islamic education. Both concepts are an ongoing contestation due to difference of perspectives and practices within Muslim community. Feminism in one hand is a movement that advocates gender equity and criticizes the marginalization of women in society. It often questions the culture of patriarchy that limit women’s agency. On the other hand, religious authority is often described as male-dominated domain. This paper aims to elaborate how feminism challenges traditional and conservative religious authority and to what extent its implications towards Islamic education? These questions are answered through a library-based qualitative method. The finding shows that feminism challenges the dominance of male religious authority. Feminism emphasizes the need for Islamic educational institutions to implement egalitarian principles of Islam that place female and male equally and to promote women’s religious role, leadership and religious authority. This will contribute to rebuild a more egalitarian Islamic education that empower women and shape a more inclusive Muslim society.